Democratic deepening in South Africa: the effect of public-private contracts on local government service delivery and local citizen participation - Mottiar, Shauna (My University, 2009)
ABSTRACT LOCAL GOVERNMENT in South Africa is well positioned to meet some of the substantive challenges posed by the democratic deepening and development discourses in new democracies. It is responsible for the delivery of services to local citizens in a way that is ‘equitable, accessible and financially sustainable’. It is also supposed to ‘develop a culture of municipal governance that compliments formal representative government with a system of participatory governance’. Democratic decentralisation in South Africa does however have its limits in fiscal and institutional terms. Furthermore the course of developmental decentralisation is affected by levels of civil society activity and political will. Also, following the global trend towards New Public Management and national pressure on local government to be economically viable, various local authorities in South Africa have opted to enter into public – private partnerships for service delivery. These contract based arrangements significantly alter the way basic services are defined and destroy the relationship between local authorities and local citizens. Services become commodities as opposed to rights, local citizens become consumers and local authorities cease to be politically accountable. This thesis examines the effect contract based service delivery has on democratic deepening in terms of local citizens being afforded their rights to basic services and having meaningful opportunities to participate in the affairs of their local authorities.